Innovations coursebook : a course in natural english - Dellar, Hugh (Thomson, 2007)
Innovations is a new five-level general English course for classes looking for new material with a fresh approach. Based on a language-rich, lexical/grammatical syllabus, it starts from the kinds of natural conversations that learners want to have. Presents and practises hundreds of natural expressions that are immediately useful in practical situations. Motivates learners by presenting interesting and unusual texts. Emphasizes sound-chunking and oral fluency. Covers productive and receptive pronunciation work. Includes built-in learner-training pages that include tips and advice. Teaches many aspects of grammar and spoken language not found in other coursebooks. Contains 20 stimulating six-page units, review units, and grammar commentary.